CMV sinusitis, an overlooked diagnosis, a predisposing condition or is it a bystander? A Case report and review of the literature. (2022) - Wilson Dib, Rita; El Haddad, Hanine; Arduino, Roberto; Ben Barnett
Abstract: The disease entity of cytomegalovirus (CMV) sinusitis has been uncommonly described in the literature, although other end organ debilitating diseases are frequently encountered in people with advanced Human immunodeficiency virus (HIV) infection. We herein present a case of CMV sinusitis in an patient with acquired immunodeficiency syndrome (AIDS) diagnosed by the detection of intranuclear viral inclusions and positive CMV immunostains. The patient responded to surgical debridement and targeted medical therapy. A consideration should be made to this rarely described form of CMV disease. There is heterogeneity in how the diagnosis was made in the reported cases in the reviewed literature. Unlike our patient, not all the patients had cytopathological evidence of the disease. Furthermore, some of the patients improved with surgical therapy alone raising the question of the true clinical significance of the recovery of CMV viral particles without cytopathic evidence in their corresponding diagnostic workup. On another note, the recovery of CMV in samples of patients with chronic antibiotic-resistant sinusitis may suggest a pathogenic role and necessitates adequate therapeutic interventions.